Microprocessor based dead reckoning table - Evren, Tayfun. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1983., 1983)
The appllcation areas or microprocessors have been growing recently. In addition to various areas, efficient and reliable results have been obtained in military applications. The object of this thesis is to apply microprocessor control on a device used in the Navy and thp realization of the necessary hardware and software and the observation of the results. In this study, the Dead Reckoning Table used on the ships of the Navy was controlled and operated by microprocessor. The Dead Reckoning Table is used for recording the movements of our ship and the others in the same operation area. Many tactical and manoeuvre problems are solved on this table. The preparing speed and the reliability of the records are increased and the operator mistakes are prevented with the aid of microprocessor.
Keywords: Dead reckoning (Navigation); Motorola 6800 (Microprocessor)